2019
DOI: 10.1093/mnras/stz2805
|View full text |Cite
|
Sign up to set email alerts
|

Dark Energy Survey year 1 results: the relationship between mass and light around cosmic voids

Abstract: What are the mass and galaxy profiles of cosmic voids? In this paper, we use two methods to extract voids in the Dark Energy Survey (DES) Year 1 redMaGiC galaxy sample to address this question. We use either 2D slices in projection, or the 3D distribution of galaxies based on photometric redshifts to identify voids. For the mass profile, we measure the tangential shear profiles of background galaxies to infer the excess surface mass density. The signal-to-noise ratio for our lensing measurement ranges between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 104 publications
2
40
0
Order By: Relevance
“…On fitting the model to data, they find a relative amplitude factor α v = 0.67 ± 0.2, close to 2σ smaller than the expectation α v = 1, and entirely consistent with our result for A naive L given their larger uncertainties. Using lensing shear measurements for a different catalog of voids obtained from galaxy samples in DES Year 1 with photometric redshifts only, Fang et al (2019) report better agreement with the assumption of a linear relationship between the void matter and galaxy density profiles, but again with an effective bias factor that is in excess of that determined from galaxy clustering for the vast majority (∼ 85%) of voids (e.g., see their Figure 14).…”
Section: Testing the Linear Bias Model In Voidsmentioning
confidence: 76%
“…On fitting the model to data, they find a relative amplitude factor α v = 0.67 ± 0.2, close to 2σ smaller than the expectation α v = 1, and entirely consistent with our result for A naive L given their larger uncertainties. Using lensing shear measurements for a different catalog of voids obtained from galaxy samples in DES Year 1 with photometric redshifts only, Fang et al (2019) report better agreement with the assumption of a linear relationship between the void matter and galaxy density profiles, but again with an effective bias factor that is in excess of that determined from galaxy clustering for the vast majority (∼ 85%) of voids (e.g., see their Figure 14).…”
Section: Testing the Linear Bias Model In Voidsmentioning
confidence: 76%
“…Hamaus et al 2020, and references therein). It has already been successfully used to study voids in the DES Y1 data (Pollina et al 2019;Fang et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the wide field, we randomly selected a subsample of the clusters with richness λ RM > 35; for the small inset, we zoom in on the (randomly chosen) location (RA, Dec) = ( 70 (see e.g. Fang et al 2019). They certainly are useful tools in void lensing studies (Davies et al 2018) and they have been widely used in previous DES analyses (see e.g.…”
Section: Cosmic Void Imprintsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies use galaxy voids, which are identified as underdense regions in the galaxy distribution (e.g., Pan et al 2012;Paz et al 2013;Sutter et al 2014;Cautun et al 2016;Nadathur 2016;Mao et al 2017;Pollina et al 2019;Hamaus et al 2020;Aubert et al 2020), where galaxy void statistics are complementary to the galaxy power spectrum and baryonic acoustic oscillations (e.g., Pisani et al 2015;Hamaus et al 2016;Nadathur et al 2019). Recently, void WL profiles have also been shown to be a powerful cosmological probe (see, e.g., Melchior et al 2014;Clampitt & Jain 2015;Cai et al 2015;Barreira et al 2015;Gruen et al 2016;Barreira et al 2017;Falck et al 2018;Baker et al 2018;Fang et al 2019).…”
Section: Introductionmentioning
confidence: 99%